Priming quantifier scope: Reexamining the evidence against scope inversion. Issue 1 (27th March 2020) - Feiman, Roman; Maldonado, Mora; Snedeker, Jesse
Abstract : In a study of quantifier-scope priming, Chemla and Bott (2015 ) found evidence suggesting that, while representations of quantifiers' relative scope can be primed, a scope inversion operation cannot. We identify a confound in their materials. In Experiment 1, we replicate their finding with this confound intact. In Experiment 2, we remove the confound and find that all priming disappears. This confound demonstrates how structural priming paradigms can be sensitive to many dimensions of similarity, pointing to a need for task-specific controls. We conclude that the prior study does not provide evidence concerning the priming of either relative scope representations or operations. While priming of scope representations has been independently found in other paradigms, the jury is still out on Chemla and Bott's more novel finding – the absence of priming of a scope inversion operation.